The relationship between non-suicidal self-injury and childhood abuse in transgender people: a cross-sectional cohort study - Cao, Qiang; Zhang, Qi; Chen, Yuquan; He, Zixu; Xiang, Zhibiao; Guan, Haoran; Yan, Na; Qiang, Yi; Li, Mantao (Frontiers in Psychology, 2023)
Objective: To explore the relationship between non-suicidal self-injury(NSSI) and childhood abuse in transgender people and the mediating effect of emotional dysregulation traits in the association between childhood abuse and non-suicidal self-injury.From May to October 2021, 296 female-to-male (FTM) and 675 male-to-females (MTF), with age of 24.5±6.4 years, were recruited using peer-driven sampling and anonymous questionnaires in Guangdong Province. The Childhood Abuse Questionnaire (CTQ-SF), the Personality Diagnostic Questionnaire (PDQ-4+) emotion regulation ability scale and the DSM-5 Clinical Examination of Stereotypic Disorders were used to measure childhood abuse experiences, emotional dysregulation traits and self-injurious behaviour respectively.Results:Childhood abuse scores were positively correlated with both emotional dysregulation traits scores and non-suicidal self-injury(NSSI) behaviors (p<0.01), and emotional dysregulation traits scores were positively correlated with NSSI behaviors (p<0.01); emotional dysregulation traits partially mediated the association between childhood abuse and NSSI behaviors, with the mediating effect accounting for 23.23% of the total effect. In addition, among the factors of childhood abuse, emotional dysregulation traits mediated the association between emotional abuse, emotional neglect, sexual abuse, physical abuse, physical neglect and NSSI behaviour significantly, with the mediating effect accounting for 22.48% to 32.58% of the total effect. 3 Conclusion:Transgender NSSI behaviours are associated with childhood abuse and emotional dysregulation traits, and emotional dysregulation traits partially mediates the association between childhood abuse and NSSI behaviours, and screening for emotional dysregulation traits in transgender people and timely interventions are needed to improve the current situation of discrimination against transgender people.